1988
DOI: 10.1103/physrevd.37.2379
|View full text |Cite
|
Sign up to set email alerts
|

Production and decay properties of the ωπ0state at 1250 MeV/c2produced by 20-GeV polarized photons on hyd

Abstract: The low mass wz" enhancement in yp + pwro has been of considerable interest in the past due to its suggested vector nature and possible role in the spectroscopy of the i ,c-. . _ rho meson radial recurrences.We have measured the properties of this photoproduced .wz" system using the SLAC Hybrid Facility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

1989
1989
2005
2005

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…They concluded that the enhancement is consistent with predominant b 1 (1235) production, with ∼ 20% J P = 1 − background. This conclusion was confirmed by a SLAC experiment [6] at an energy of 20 GeV, W = 6.2 GeV, with a polarised beam. It should be noted that a spin-parity analysis of the H1 data cannot be performed because of limited acceptance.…”
supporting
confidence: 57%
“…They concluded that the enhancement is consistent with predominant b 1 (1235) production, with ∼ 20% J P = 1 − background. This conclusion was confirmed by a SLAC experiment [6] at an energy of 20 GeV, W = 6.2 GeV, with a polarised beam. It should be noted that a spin-parity analysis of the H1 data cannot be performed because of limited acceptance.…”
supporting
confidence: 57%
“…Additionally the production mechanism does not appear to conserve s-channel helicity. This latter conclusion is confirmed in the experiment of [9] which had the benefit of a linearly-polarised beam. The angular distribution of the production plane relative to the photon polarisation vector has structure which is inconsistent with s-channel helicity conservation.…”
Section: Introductionmentioning
confidence: 53%
“…The angular distribution of the production plane relative to the photon polarisation vector has structure which is inconsistent with s-channel helicity conservation. The decay angular distributions of the two experiments agree and it was also concluded by [9] that the data favour a b 1 (1235) interpretation over a vector-meson interpretation. Preliminary data [10] on ωπ photoproduction at high energy indicate a cross section for the 1250 MeV enhancement which is comparable to or larger than the cross section at much lower energy [8,9], with the natural inference that it is being produced diffractively.…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations